2007
DOI: 10.1007/s11418-007-0185-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between 1-deoxynojirimycin content and α-glucosidase inhibitory activity in leaves of 276 mulberry cultivars (Morus spp.) in Kyoto, Japan

Abstract: The relationship between 1-deoxynojirimycin (DNJ) content and alpha-glucosidase inhibitory activity in mulberry (Morus) leaves is discussed. Mulberry leaves were collected from the Center for Bioresource Field Science, Kyoto Institute of Technology, Kyoto, Japan on 19 May, 9 July, and 9 August, 2003. Mulberry leaves were extracted with 75% ethanol. The inhibitory activity for rat intestinal crude enzyme was measured using maltose. The content of DNJ in the extracts was measured using HPLC. The mean DNJ content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 10 publications
2
40
1
Order By: Relevance
“…[8][9][10][11] Yatsunami et al have reported the relationship between the -glucosidase inhibitory activity and 1-DNJ concentration from a group of species, 10) but not enough is known about -glucosidase inhibitors other than 1-DNJ from each cultivar. Since the -glucosidase inhibitory activity was not consistent with the 1-DNJ concentration in several cultivars, it is thought that -glucosidase inhibitors besides 1-DNJ were involved in the effective defense by mulberry plants against insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Yatsunami et al have reported the relationship between the -glucosidase inhibitory activity and 1-DNJ concentration from a group of species, 10) but not enough is known about -glucosidase inhibitors other than 1-DNJ from each cultivar. Since the -glucosidase inhibitory activity was not consistent with the 1-DNJ concentration in several cultivars, it is thought that -glucosidase inhibitors besides 1-DNJ were involved in the effective defense by mulberry plants against insect herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…The typical cultivars of mulberry plants are maintained and administered in Japan at the National Institute of Agrobiological Sciences (Tsukuba, Ibaraki, Japan) and the Experimental Farm of Textile Science and Technology of Shinshu University (Ueda, Nagano, Japan). It has been reported that the -glucosidase inhibitory activity and 1-DNJ concentration of mulberry leaves differ among various cultivars and seasons, [8][9][10][11] but it is unknown which environmental conditions influence the -glucosidase inhibitory activity. We therefore investigated in this study the relationship between the environmental conditions and -glucosidase inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
“…White Mulberry being traditionally recognized as a medicinal species and its leaves being the food of the silk, there are extensive reports on the leaves or root-bark extracts of white mulberry (Chen and Li 2007, Yatsunami et al 2008, Nakamura et al 2009, Piao et al 2009, Zheng et al 2010. The wood is also been reported to be durable (Se Golpayegani et al 2010, Se Golpayegani 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry leaf contains minerals, vitamins, dietary fiber, amino acids, phytosterols, flavonoids and other functional components, and has various kinds of biological activities including hypoglycemic activity (Nojima et al, 1998;Kimumar et al, 1995;Kimura et al, 2007), antiobesity action (Tsuduki et al, 2013), antioxidant activity (Doi et al, 2000), antiviral activity (Tierney et al, 1995;Thipamon et al, 2010), hypolipidemic activity (Doi et al, 2000;Kojima et al, 2010), antineoplastic activity (Kim et al, 2000), antimutagenicity activity (Thipamon et al, 2010), etc. Most impressively, mulberry leaf is rich in N-containing sugars including DNJ, which is known as one of the most potent α-glycosidase inhibitors (Asano et al, 1994;Yatsunami et al, 2008). It makes mulberry tea not only has hypoglycemic activity but also has a significant role in targeted prevention and treatment of its complications.…”
Section: Introductionmentioning
confidence: 99%